The same CCAAT box-binding factor binds to the promoter of two coordinately regulated major histocompatibility complex class II genes. - Kern, M J (1991)
Using competition mobility shift, methylation interference, and proteolytic clipping DNA binding assays, we demonstrate that the protein binding the major histocompatibility complex A beta CCAAT box is indistinguishable from the protein previously named NF-Y, which binds the major histocompatibility complex E alpha CCAAT box. Although the two CCAAT boxes share the same 10-base core sequence, termed the Y box, their flanking sequences, known to be important for binding, are very different.